Halal Certification in Government and Non-Governmental Organizations: A Comparative Analysis of Indonesia, Malaysia, and Thailand - Yakub, Aminudin; Zein, Fitriyani (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2022)
The enactment of Law Number 33 of 2014 concerning Halal Product Assurance (JPH) changed the implementation of Halal Certification in Indonesia where halal certification which had been carried out by MUI for 30 years (since 1989) changed to the Halal Product Assurance Organizing Agency (BPJPH) of the Ministry of Religion of the Republic of Indonesia. With this provision, a new era in the administration of Halal Product Guarantee by the government begins. This research uses qualitative research with juridical-normative and comparative approach. The author makes a comparison with Thailand and Malaysia. The results of the study state that the implementation of halal certification in Malaysia is carried out entirely by a state institution called JAKIM, while in Thailand it is carried out by non-governmental organizations (NGOs).Keywords: Halal Product Certification; Non-Governmental Organizations (NGOs); Ratio Sertifikasi Halal Melalui Pemerintah dan Organisasi Non-Pemerintah: Analisis Perbandingan Indonesia, Malaysia, dan Thailand Abstrak:Lahirnya Undang-undang Nomor 33 Tahun 2014 tentang Jaminan Produk Halal (JPH) mengubah pelaksanaan Sertifikasi Halal di Indonesia dimana sertifikasi halal yang telah dijalankan MUI selama 30 tahun (sejak 1989) berubah ke Badan Penyelenggara Jaminan Produk Halal (BPJPH) Kementerian Agama RI. Dengan ketentuan ini maka dimulai era baru penyelenggaraan Jaminan Produk Halal oleh pemerintah. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan yuridis-normative dan perbandingan. Penulis melakukan perbandingan dengan negara Thailand dan Malaysia. Hasil penelitian menyatakan bahwa pelaksanaan sertifikasi halal di Malaysia dilakukan sepenuhnya oleh lembaga negara yang bernama JAKIM, sedangkan di Thailand dilakukan oleh lembaga non pemerintah (NGO).Kata Kunci: Sertifikasi Produk Halal; Organisisasi Non Pemerintah (NGO); Perbandingan Халяльная сертификация в государственных и негосударственных организациях: сравнительный анализ Индонезии, Малайзии и Таиланда Аннотация:Принятие Закона № 33 от 2014 г. о Гарантии на халяльный продукт (JPH) изменило внедрение халяльной сертификации в Индонезии, где халяльная сертификация, которая проводилась MUI (Советом Индонезийских Богослов) в течение 30 лет (с 1989 г.), была преобразована в Организационный орган по обеспечению халяльной продукции (BPJPH) Министерства по делам религии Республики Индонезии. С этим положением начинается новая эра в управлении гарантией на халяльный продукт со стороны правительства. В данном исследовании используются качественные исследования с юридически-нормативным и сравнительным подходами. Автор проводит сравнение с Таиландом и Малайзией. Результаты исследования показывают, что внедрение халяльной сертификации в Малайзии полностью осуществляется государственным учреждением под названием JAKIM, а в Таиланде - неправительственными организациями (NGO).Ключевые слова: Сертификация халяльной продукции; Неправительственные организации (NGOs); Соотношение